UNDERSTANDING PATIENTS' PERSPECTIVES ON PRIVACY AND CONFIDENTIALITY OF HEALTH INFORMATION IN NIGERIA: A CASE STUDY OF MEDICAL OUTPATIENTS AT LAGOS UNIVERSITY TEACHING HOSPITAL (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Introduction: Ensuring patient confidentiality and privacy in healthcare interactions is not only a legal imperative but also a cornerstone of effective and ethical patient care. These principles profoundly impact the patient-provider relationship, influencing the degree of trust, open communication, and the overall quality of healthcare delivery. In contemporary healthcare settings, the importance of safeguarding patient information has gained increased recognition, driven by a confluence of legal, technological, and societal factors. As healthcare systems evolve, maintaining the delicate balance between the need for information sharing and the imperative to protect patients' personal data becomes increasingly complex. This study delves into the multifaceted aspects of patients' awareness, attitudes, and trust concerning privacy and confidentiality within the healthcare context. By focusing on the Medical Outpatient Departments (MOPD) at Lagos University Teaching Hospital (LUTH), the research aims to provide nuanced insights into the dynamics that shape patient perceptions. Understanding these dynamics is crucial not only for optimizing patient-centered care but also for informing educational strategies and policy development.